Early comprehensive pulmonary rehabilitation for hospitalized patients with acute ex-acerbation of chronic obstructive pulmonary disease: a randomized controlled trial - Yuqin Zeng; Qian Wu; Yan Chen; Shan Cai (Medical Journals Sweden, 2024)
Objective: To investigate whether an early comprehensive pulmonary rehabilitation intervention initiated during hospital admission is safe and effective for patients with acute exacerbation of chronic obstructive pulmonary disease. Design: Prospective randomized controlled study. Subjects/Patients: Patients with acute exacerbation of chronic obstructive pulmonary disease. Methods: In total, 108 patients were randomized to the early comprehensive pulmonary rehabilitation and usual care groups within 48 hours. The 6-min walking distance, quality of life, breathlessness, and inspiratory muscle strength were measured on admission and discharge. Any adverse events of pulmonary rehabilitation were recorded. Results: On discharge, the patients in the early comprehensive pulmonary rehabilitation group had a more significant improvement in the 6-min walking distance (47.5 vs 23.0, p = 0.04). There was no significant difference in quality of life and breathlessness between the 2 groups. In the early comprehensive pulmonary rehabilitation group, inspiratory muscle strength and peak inspiratory flow were significantly improved, and the changes were much more pronounced than in the usual care group. There were no adverse events. Conclusion: Early comprehensive pulmonary rehabilitation is safe and effective for hospitalized patients with acute exacerbation of chronic obstructive pulmonary disease, and should be performed during the early stage of hospitalization.